2012
DOI: 10.1016/j.jad.2011.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Type D (distressed) personality is associated with poor quality of life and mental health among 3080 cancer survivors

Abstract: Cancer survivors with a Type D personality are at increased risk of impaired QoL and mental health problems that cannot be explained by socio-demographic or clinical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 33 publications
7
63
3
4
Order By: Relevance
“…In our sample the proportion of type D personality was 27%, while in a study from the Netherlands, Mols et al [18] reported 17% (p ¼ 0.03). This difference may be due to sampling differences, but another explanation could be the significant differences in time since diagnosis (mean 4.5 years in their sample and 12.5 years in ours).…”
Section: Patterns Of Employmentcontrasting
confidence: 67%
“…In our sample the proportion of type D personality was 27%, while in a study from the Netherlands, Mols et al [18] reported 17% (p ¼ 0.03). This difference may be due to sampling differences, but another explanation could be the significant differences in time since diagnosis (mean 4.5 years in their sample and 12.5 years in ours).…”
Section: Patterns Of Employmentcontrasting
confidence: 67%
“…It is well-known that suffering from cancer and additionally undergoing cancer treatment has a major impact on patients' lives, with the majority of cancer patients experiencing psychological problems, such as feelings of anxiety, fatigue and depression [23,24]. Moreover, one in 5 cancer patients have a Type D personality [25]. Hence, cancer patients may have an increased risk for onset CVD by these elevated levels of psychological distress after cancer diagnosis alone.…”
Section: Psychological Distress (D)mentioning
confidence: 99%
“…Moreover, one in 5 cancer patients have a Type D personality [25]. Hence, cancer patients may have an increased risk for onset CVD by these elevated levels of psychological distress after cancer diagnosis alone.…”
Section: Psychological Distress (D)mentioning
confidence: 99%
“…All individuals diagnosed with endometrial or colorectal cancer (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007), thyroid cancer (1990-2008), Hodgkin or non-Hodgkin lymphoma, or multiple myeloma (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) were eligible for participation. Details of sample selection for the survivorship studies are reported elsewhere [30][31][32][33].…”
Section: Setting and Participantsmentioning
confidence: 99%